COMPARATIVE ASPECTS CONCERNING METHODS USED TO DETERMINE COTTON FIBERS STRENGTH PER DENIER - HRISTIAN Liliana; BORDEIANU Demetra Lăcrămioara; BŐHM-RÉVÉSZ Gabriella (Annals of the University of Oradea: Fascicle of Textiles, Leatherwork, 2015)
This work has shown to you a study about the determination of tensile strenght by three methods of stress, using the four varieties of the cotton fibers: Russian 2A, Russian 1A, Sudanese Baracat 5x5, Pakistani SLM (Medium IV). The methods of the tensile stress used in this study are: the method of requesting of a bundle containing all categories of fibers from the sample, using the DS-3M dynamometer; the the method of application of flat bundles of fibers containing fibers previously sorted by length classes using the mechanical fibrometer and then subjected to tensile strength determination on the dynamometer DS-3M; the method of application of the three fiber bundles corresponding to the class with the highest fiber content. From the comparative analysis of these three methods of stress,we can find that the index for assessing the tensile strength, called the toughness mode, obtained by the third method, combining the advantages of the first method and eliminating the disadvantages of the second, can be an optimal index to express it. From the experimental results and the graphical representations as the distribution diagram of the cotton fiber length, depending on their mass,we can find that the fiber mass belonged to the classes with the highest fiber content is about 35-55% of the total mass of the sample, an enough approximation for the tenacity, the toughness mode, to be expressed, using a coefficient ,named the average tenacity, measured by the disclosed methods . The third proposed method has a double productivity of conventional methods, it reduces the time required for all determinations by 55%, it is not required the counting of the fibers per a milligram and also, it is possible to determine the mode length of the fibers at the same time /with the tenacity.